"I Expected More From You": The Effect of Expectation-Disconfirmation on Employees' Satisfaction With Supervisory Support. (June 2023) - Penning de Vries, Julia; Knies, Eva
Are employees less satisfied with supervisor support when their expectations are disconfirmed? In this study, we examine this question for both predictive expectations (what will happen) and normative expectations (what should happen). Results from two preregistered experiments suggest that expectation-disconfirmation does not affect satisfaction with supervisor support. Instead, we find that expectation-disconfirmation as perceived by participants affects satisfaction with supervisor support. We conclude that even though supervisor support seems to be the most important predictor of satisfaction, perceived disconfirmation of expectations also influences employees' satisfaction with supervisor support.